(untitled) (Kinesiology, 2023)
High-intensity functional training (HIFT) can play a major role in preventing cardiometabolic disease. The majority of HIFT interventions incorporate CrossFit (CF) training. We measured aerobic capacity, metabolic response during high-intensity interval exercise (HIIE), resting mitochondrial oxidative capacity, and resting vascular function in adults who participated in CF training (> one year) vs. a sedentary group completing <2 h·wk-1 of structure exercise for > one year (SED). Twenty-one participants were recruited (CF n = 13 vs. SED n = 8). CF participants had a 33.0% greater relative VO2 peak (p<.001) and lower body fat percentage (CF = 18.6 [3.8] vs. SED = 30.3 [8.4]; p<.001). CF participants had higher exercising substrate oxidation when expressed as absolute and body weight relative values (p<.013), but not when expressed relative to lean mass (p>.200). CF participants had greater mitochondrial oxidative capacity (p=.014). There were no differences in large artery function, but CF participants had greater baseline arterial diameter (p=.004) and faster reperfusion following arterial occlusion (p<.05). These data support HIFT programs’ effectiveness in improving fitness, weight status, and metabolic, mitochondrial, and vascular function. Key words: high-intensity functional training, CrossFit, metabolism, vascular function